1986
DOI: 10.1007/bf00174073
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the possible role of brain 5-HT systems and adrenocortical activity in behavioural responses to nicotine and diazepam in an elevated X-maze

Abstract: Subchronic (6 days) but not acute injections of nicotine (0.4 mg/kg SC) increased spontaneous activity (P less than 0.01) in an elevated X-maze composed of two open and two enclosed runways. Neither acute nor subchronic nicotine altered significantly the ratio of open:enclosed runway entries (O/E ratio). Diazepam (5 mg/kg PO) had no significant effects on spontaneous activity but increased the O/E ratio (P less than 0.05). Acute nicotine increased (P less than 0.01) whereas subchronic nicotine caused a small d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…However, since consistent reductions in 5-HIAA were observed in both hypothalamus and cerebral cortex of lesioned rats, it is perhaps more likely that, in these rats at least, the loss of 5-HT secreting terminals in the hippocampus may have been associated with reduced 5-HT secretion in these other two brain regions. The data reported here for the effects of nicotine on the behaviour of the rats in the maze are in very good agreement with the results of previous studies with unoperated rats in this maze (Balfour et al, 1986). Specifically both this and the earlier study have shown the subchronic, but not acute, licotine causes a stimulation of spontaneous activity while having no effect on the O/E ratio.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, since consistent reductions in 5-HIAA were observed in both hypothalamus and cerebral cortex of lesioned rats, it is perhaps more likely that, in these rats at least, the loss of 5-HT secreting terminals in the hippocampus may have been associated with reduced 5-HT secretion in these other two brain regions. The data reported here for the effects of nicotine on the behaviour of the rats in the maze are in very good agreement with the results of previous studies with unoperated rats in this maze (Balfour et al, 1986). Specifically both this and the earlier study have shown the subchronic, but not acute, licotine causes a stimulation of spontaneous activity while having no effect on the O/E ratio.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies (Balfour et al, 1986) have shown that the increase in O/E ratio observed in rats given diazepam appears to be associated with a reduction in the plasma corticosterone concentration. These earlier experiments also showed that the increased plasma corticosterone levels observed in rats given acute nicotine were not associated with a decrease in the ratio.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, nicotine effects on serotonin and somatostatin innervation of the hippocampus have been documented (Balfour et al 1986;Barrios et al 1990). The behavioral significance of these interactions with nicotine effects on memory function is currently unclear.…”
Section: Other Transmitter Systemsmentioning
confidence: 97%
“…The elevated plus-maze, consisting of two open and two enclosed arms, is based on the apparent natural aversion of rodents to open and high spaces, and is used for measurement of anxiety (Pellow et al 1985;Balfour et al 1986;Pellow and File 1986;Lister 1987). Animals spend more time in the enclosed arms than the open Offprint requests to."…”
mentioning
confidence: 99%